# How to Prove It - Solutions

## Chapter - 5, Functions

### Summary

• Suppose $f : A \to B$. We will say that $f$ is one-to-one if:
$\lnot \exists a_1 \in A \exists a_2 \in A(f(a_1)= f(a_2) \land a_1 \ne a_2)$.
We say that $f$ is onto if:
$\forall b \in B \exists a \in A(f(a) = b)$.
One-to-one functions are sometimes also called injections, and onto functions are sometimes called surjections.
• Suppose $f : A \to B$. Then:
• $f$ is one-to-one iff $\forall a_1 \in A \forall a_2 \in A(f(a_1) = f(a_2) \to a_1 = a_2)$. Note that this statement is the positive form of the statement given above for one-to-one.
As can be seen here, this statement is easier to prove that a function is one-to-one. We select two values $a_1, a_2 \in A$ such that $f(a_1) = f(a_2)$. Now by doing so if we can conclude that $a_1 = a_2$ then function is one-to-one.
• $f$ is onto iff $Ran(f) = B$.
• Suppose $f: A \to B$ and $g: B \to C$. Then as we know by the definition of composition of functions: $g \circ f : A \to C$.
• If $f$ and $g$ are both one-to-one,then so is $g \circ f$.
• If $f$ and $g$ are both onto, then so is $g \circ f$.
• If a function is one-to-one and onto, the function is sometimes called bijective.

Soln1

(a) One-to-One: False, Onto: True

(b) It is not a function, so question is not applicable.

(c) One-to-One: True, Onto: False

Soln2

(a) It is not a function, so question is not applicable.

(b) $f$ is not a function. $g$: One-to-One: False, as $(ball,b),(bat,b) \in g$. Onto: True.

(c) One-to-One: True, Onto: True

Soln3

(a) One-to-One: False, Onto: True

(b)

For $x = 2, f(x) = 0$, Also for $x = 0, f(x) = 0$. Thus for two values, there is only one image in the range. Thus function is not one-to-one.

It is not onto. To prove it lets suppose $f$ is onto. Thus for $a \in \mathbb R$, there must exist some $x \in \mathbb R$ such that $f(x) = a$. Thus $x^2 - 2x = a$.
$\Rightarrow x^2 - 2x + 1 = a + 1$.
$\Rightarrow (x-1)^2 = a + 1$.
$\Rightarrow x = \sqrt {a + 1} + 1$.

Now, clearly we can see that if $% $, $x \notin \mathbb R$. Thus $f$ is not onto.

(c)

One-to-one: False, because $f(3.2) = f(3.3)$.

Onto: True, For every $c \in \mathbb R$, for $x = \left \lfloor c \right \rfloor$, $f(x) = c$.

Soln4

(a) One-to-one: True. Onto: False as there are many cities which are not capital of any country.

(b) One-to-one: True, Onto: True.

(c) One-to-one: True, Onto: False because for $y = (0.7,0.7)$, there is not value of $x$ such that $f(x) = (0.7,0.7)$.

Soln5

(a)

One-to-one:

Suppose $x_1, x_2 \in A$ such that $f(x_1) = f(x_2)$. Thus we have:

$\Rightarrow \frac {x_1 + 1} {x_1 - 1} = \frac {x_2 + 1} {x_2 - 1}$.
$\Rightarrow (x_1 + 1)(x_2 - 1) = (x_2 + 1)(x_1 - 1)$.
$\Rightarrow x_1x_2 - x_1 + x_2 - 1 = x_1 x_2 - x_2 + x_1 -1$.
$\Rightarrow - x_1 + x_2 = - x_2 + x_1$.
$\Rightarrow 2x_2 = 2x_1$.
$\Rightarrow x_2 = x_1$.

Thus, if $f(x_1) = f(x_2)$, then $x_1 = x_ 2$. Since $x_1, x_2$ are arbitrary, it follows that $f$ is one-to-one.

Onto:

Suppose $y \in A$ is an arbitrary number such that $f(x) = y$. Thus we have:

$\Rightarrow y = \frac {x + 1} {x - 1}$.
$\Rightarrow y(x - 1) = (x + 1)$.
$\Rightarrow yx - y = x + 1$.
$\Rightarrow yx - x = y + 1$.
$\Rightarrow x(y - 1) = y + 1$.
$\Rightarrow x = \frac {y + 1} {y - 1}$.

Since $y \in A$ and $x = \frac {y + 1} {y - 1}$, it follows that $x \in A$. Since $y$ is arbitrary, it follows that for every $y \in A$, there exists an $x = \frac {y + 1} {y - 1}$ such that $f(x) = y$. Thus $f$ is onto.

(b)

$f \circ f (x) = f(f(x)) = f(\frac {x + 1} {x - 1}) = \frac {\frac {x+1} {x-1} + 1} {\frac {x+1} {x-1} - 1}$.
$f \circ f (x) = \frac {\frac {x+1 + (x-1)} {x-1}} {\frac {x+1 - (x -1)} {x-1}}$.
$f \circ f (x) = \frac {\frac {2x} {x-1}} {\frac {2} {x-1}}$.
$f \circ f (x) = \frac {2x} {x-1} \times \frac {x-1} {2}$.
$f \circ f (x) = x$.

Thus $f \circ f = i_A$.

Soln6

(a) $% $.

(b) $f$ is not one-to-one because $f(-1) = f(-2) = \phi$. $f$ is onto because for any set $y = \{ q \in R \}$, if $x = 1 + {(\text{largest element of y})}^2$, then $(x,y) \in f$.

Update:

Part(b) of this answer is wrong regarding the onto part(for one-to-one it is correct). Please check here.

I define $x = 1 + {(\text{largest element of y})}^2$ By this definition not every pair of $(x,y)$ belongs to $f$ or for same $x$ there can be multiple $y$.

Now the correct answer(from stackoverflow) answer is, if $x > 0$ then $f(x) = (- \sqrt x, \sqrt x )$. Clearly there are many sets which do not fall in this category for eg: $(5, 23) \notin f$.

Soln7

(a) $f(\{\{1,2\},\{3,4\}\}) = \{1,2,3,4\}$.

(b) It is not one-to-one since $f(\{\{1,2\},\{3,4\}\}) = f(\{\{1,3\},\{2,4\}\})$. However it is onto.

Soln8

(a)

Suppose $g \circ f: A \to C$ is onto. Suppose $c \in C$ is any arbitrary number. Since $g \circ f$ is onto, it follows that there must exist an element $a \in A$ such that $a = g \circ f(c)$. Thus $g(f(a)) = c$. Since $c$ is arbitrary, it follows that for every element $c \in C$, there exist an element $b = f(a)$ such that $g(b) = c$. Thus $g$ is onto.

(b)

Suppose $g \circ f: A \to C$ is one-to-one. Suppose $a_1, a_2 \in A$ such that $f(a_1) = f(a_2)$. Since $g$ is a function, it follows that $g(f (x_1)) = g(f(x_2))$. It follows that $g \circ f(x_1) = g \circ f (x_2)$. Since $g \circ f$ is a one-to-one, it follows that $x_1 = x_2$. Thus if $f(x_1) = f(x_2)$, then $x_1 = x_2$. Since $x_1, x_2$ are arbitrary, it follows that $f$ is one-to-one.

Soln9

(a)

Since $g$ is not one-to-one, suppose $b_1,b_2 \in B$ such that $g(b_1) = g(b_2)$. Since $f$ is onto, it follows that there exist some $a_1, a_2 \in A$ such that $f(a_1) = b_1$ and $f(a_2) = b_2$. Thus we have $g(f(a_1)) = g(f(a_2))$, or $g \circ f(a_1) = g \circ f(a_2)$. Thus $g \circ f$ is not one-to-one.

(b)

Since $f$ is not onto, suppose $b \in B$ such that $\forall a \in A (f(a) \ne b )$. Since $g$ is a function from $B$ to $C$, it follows that for some $c \in C$, $c = g(b)$. We shall prove by contradiction. Thus suppose $g \circ f$ is onto. Thus for some $a \in A$, $g \circ f (a) = c$. Thus $g(f(a)) = c$. Since $g(b) = c$, and $g$ is one-to-one, it follows $f(a) = b$. But it contradicts that $\forall a \in A (f(a) \ne b )$. Thus $g \circ f$ is not onto.

Soln10

(a)

Suppose $f$ is one-to-one. Suppose $c_1, c_2 \in C$ such that $f \upharpoonleft C (c_1) = f \upharpoonleft C (c_2)$. Thus there exist an element $b \in B$ such that $(c_1,b) \in f \land (c_1,b) \in B \times C$ and $(c_2,b) \in f \land (c_2,b) \in B \times C$. Since $f$ is one-to-one and $(c_1,b) \in f \land (c_2,b) \in f$, it follows that $c_1 = c_2$. Thus if $f \upharpoonleft C (c_1) = f \upharpoonleft C (c_2)$, then $c_1 = c_2$. Since $c_1, c_2$ are arbitrary, it follows that $f \upharpoonleft C$ is one-to-one.

(b)

Suppose $f \upharpoonleft C$ is onto. Suppose $b \in B$ is an arbitrary element. Since $f \upharpoonleft C$ is onto, there must exist some element $c \in C$ such that $f \upharpoonleft C(c) = b$. It follows that $(c,b) \in f$. Since $c \in C$, and $C \subseteq A$, it follows $c \in A$. Since $b$ is arbitrary, it follows that for every $b \in B$, there exist some $c \in A$. Thus $f$ is onto.

(c)

Converse of (a) is: if $f \upharpoonleft C$ is one-to-one, then $f$ is one-to-one.

Suppose $A = \{1,2,3\}, B = \{a,b\}, C = \{1,2\}, f \upharpoonleft C = \{ (1,a), (2,b) \} , f = \{ (1,a), (2,b), (3,a) \}$.

Clearly, $f \upharpoonleft C$ is one-to-one but $f$ is not one-to-one.

Converse of (b) is: if $f$ is onto, then $f \upharpoonleft C$ is onto.

Suppose $A = \{1,2\}, B = \{a,b\}, C = \{2\}, f = \{ (1,a), (2,b) \}, f \upharpoonleft C = \{ (2,b) \}$.

Clearly, $f$ is onto but $f \upharpoonleft C$ is not onto.

Soln11

(a)

Suppose $A$ contains more than one elements and suppose $a_1, a_2 \in A$. Thus $f(a_1) = f(a_2) = b$. Thus $f$ is not one-to-one.

(b)

Suppose $B$ contains more than one elements and suppose $b_1 \in B$ and $b \ne b_1$. Thus there exist an element $b_1 \in B$ such that it is not the image of any element in $A$. Thus $f$ is onto.

Soln12

($\to$)Suppose $f \cup g$ is one-to-one. We will prove by contradiction that $Ran(f) \cap Ran(g) = \phi$. Suppose $Ran(f) \cap Ran(g) \ne \phi$. Thus there exist atleast one element $x$ such that $x \in Ran(f)$ and $x \in Ran(g)$. Since $x \in Ran(f)$, thus there exist an element $a \in A$ such that $(a,x) \in f$. Similarly since $x \in g$, there exist an element $b \in B$ such that $(b,x) \in g$. Since $(a,x) \in f$, and $f \cup g$ is a function, it follows $(a,x) \in f \cup g$. Similarly $(b,x) \in f \cup g$. Since $f \cup g$ is a one-to-one function, it follows that $a = b$. But since $A$ and $B$ are disjoint, it is a contradiction. Thus $Ran(f) \cap Ran(g) = \phi$.

($\leftarrow$)We shall prove this by contra-positive. Suppose $Ran(f) \cap Ran(g) \ne \phi$. Thus we can suppose an element $x \in Ran(f) \cap Ran(g)$. Since $x \in Ran(f)$, there must exist an element $a \in A$ such that $(a,x) \in f$. Similarly since $x \in Ran(g)$, there must exist an element $b \in B$ such that $(b,x) \in g$. Since $A \cap B = \phi$, it follows that $a \ne b$. Since $(a,x) \in f$, $(a,x) \in f \cup g$. Since $(b,x) \in g$, $(b,x) \in f \cup g$. Since $(a,x) \in f \cup g$ and $(b,x) \in f \cup g$ and $a \ne b$, it follows that $f \cup g$ is not one-to-one. Thus if $Ran(f) \cap Ran(g) = \phi$, then $f \cup g$ is one-to-one.

Soln13

To prove $R : A \to B$, we need to prove two things:

• $\forall a \in A \exists b \in B((a,b) \in R)$.
• if $(a,b_1) \in R$ and $(a,b_2) \in R$, then $b_1 = b_2$.

Proof for: $\forall a \in A \exists b \in B((a,b) \in R)$.

Suppose $a \in A$. Since $S \circ R$ is a function from $A$ to $C$, there must exist an element $c \in C$ such that $(a,c) \in S \circ R$. Since $(a,c) \in S \circ R$, it follows that there exist an element $b \in B$ such that $(a,b) \in R$ and $(b,c) \in S$. Thus if $a \in A$ then there exist an element $b \in B$ such that $(a,b) \in R$. Thus $\forall a \in A \exists b \in B((a,b) \in R)$.

Proof for: if $(a,b_1) \in R$ and $(a,b_2) \in R$, then $b_1 = b_2$.

Suppose $a \in A$ and $b_1, b_2 \in B$ such that $(a,b_1) \in R$ and $(a,b_2) \in R$. Since $S$ is a function, there exist $c_1, c_2 \in C$ such that $(b_1,c_1) \in S$ and $(b_2,c_2) \in S$. Since $(a,b_1) \in R$ and $(b_1,c_1) \in S$, it follows $(a,c_1) \in S \circ R$. Similarly since $(a,b_2) \in R$ and $(b_2,c_2) \in S$, it follows $(a,c_2) \in S \circ R$. Since $S \circ R$ is a function, it follows that $c_1 = c_2$. Since $(b_1,c_1) \in S$ and $(b_2,c_2) \in S$ and $c_1 = c_2$ and $S$ is a one-to-one function, it follows that $b_1 = b_2$. Thus if $(a,b_1) \in R$ and $(a,b_2) \in R$, then $b_1 = b_2$.

Thus $R$ is a function from $A$ to $B$.

Soln14

(a)

Suppose $R$ is reflexive and $f$ is onto. Suppose $x$ is an arbitrary element in $B$. Since $f$ is onto function on $A \to B$, there exist an element $u \in A$ such that $f(u) = x$. Since $R$ is reflexive and $u \in A$, it follows that $(u,u) \in R$. Thus $f(u) = x \land f(u) = x \land (u,u) \in R$. Thus $(x,x) \in S$. Since $x$ is arbitrary, it follows that $S$ is reflexive.

(b)

Suppose $R$ is transitive and $f$ is one-to-one. Suppose $(x,y) \in S$ and $(y,z) \in S$. Thus $(u,v_1) \in R$ and $(v_2,w) \in R$ such that $f(u) = x$ and $f(v_1) = y$ and $f(v_2) = y$ and $f(w) = z$. Since $f$ is one-to-one, it follows that $v_1 = v_2$ or lets say $v = v_1 = v_2$. Thus $(u,v) \in R$ and $(v,w) \in R$. Since $R$ is transitive, it follows $(u,w) \in R$. Since $f(u) = x$ and $f(w) = z$ and $(u,w) \in R$, it follows that $(x,z) \in S$. Thus $S$ is transitive.

Soln15

(a)

Suppose $[x]_R \in A/R$. Since $R$ is an equivalence relation, we know that $[x]_R$ is an equivalence class with respect to $R$. Thus by definition of equivalence class as $[x]_R$ is an equivalence class, it follows $x \in A$. Thus for every element $[x]_R \in A/R$, $x \in A$. Thus $g$ is onto.

(b)

($\to$) Suppose $g$ is one-to-one.

Since $R$ is equivalence relation, it follows that $i_A \subseteq R$.

Now to prove $R \subseteq i_A$. Suppose $(x,y) \in R$. Since $R$ is equivalence relation, $[x]_R = [y]_R$. Also since $g$ is a function on $A \to A/R$, it follows $(x,[x]_R) \in g$ and $(y,[y]_R) \in g$. Since $[x]_R = [y]_R$, and since $g$ is one-to-one, it follows $x = y$. Thus $(x,y) \in i_A$. Since $(x,y)$ is arbitrary, it follows that $R \subseteq i_A$.

Since $i_A \subseteq R$ and $R \subseteq i_A$, it follows $R = i_A$.

($\leftarrow$) Suppose $R = i_A$. Suppose $(x,X) \in g$ and suppose $(y,X) \in g$. Since $X$ is an equivalence class and $g(x) = [x]_R$, it follows that $X = [x]_R$. Similarly $X = [y]_R$. Thus $x \in X$ and $y \in X$. Since $X$ is equivalence class, it follows $xRy$. Now since $R = i_A$, it follows that $x = y$. Thus $g$ is one-to-one.

Soln16

($\to$)Suppose $h$ is one-to-one. Suppose $x,y \in A$ such that $f(x) = f(y)$. Since $x \in A$, then by the definition of $h$, $h([x]_R) = f(x)$. Similarly $h([y]_R) = f(y)$. Since $h$ is one-to-one and $f(x) = f(y)$, it follows that $[x]_R = [y]_R$. Thus $x \in [y]_R$, or $xRy$. Since $x,y$ are arbitrary, it follows that $\forall x \in A \forall y \in A (f(x) = f(y) \to xRy)$.

($\leftarrow$)Suppose $\forall x \in A \forall y \in A (f(x) = f(y) \to xRy)$. Suppose $[x]_R, [y]_R \in A/R$ such that $h([x]_R) = h([y]_R)$. Since $h([x]_R) = f(x)$ and $h([y]_R) = f(y)$, it follows that $f(x) = f(y)$. Since $\forall x \in A \forall y \in A (f(x) = f(y) \to xRy)$, it follows that $xRy$. Since $R$ is an equivalence relation and $xRy$, it follows that $[x]_R = [y]_R$. Thus $h$\$ is one-to-one.

Soln17

(a)

($\to$)Suppose $(b,c) \in g$. Since $f$ is onto, there exist an element $a \in A$ such that $(a,b) \in f$. Since $(a,b) \in f \land (b,c) \in g$, it follows that $(a,c) \in g \circ f$. Since $g \circ f = h \circ f$, it follows $(a,c) \in h \circ f$. Thus there exist an element $b' \in B$ such that $(a,b') \in f$ and $(b',c) \in h$. Since $f$ is a function, $f(a)$ is a unique element, it follows that $b' = b$. Thus $(b,c) \in h$. Thus $g \subseteq h$.

($\leftarrow$)Suppose $(b,c) \in h$. Since $f$ is onto, there exist an element $a \in A$ such that $(a,b) \in f$. Since $(a,b) \in f \land (b,c) \in h$, it follows that $(a,c) \in h \circ f$. Since $g \circ f = h \circ f$, it follows $(a,c) \in g \circ f$. Thus there exist an element $b' \in B$ such that $(a,b') \in f$ and $(b',c) \in g$. Since $f$ is a function, $f(a)$ is a unique element, it follows that $b' = b$. Thus $(b,c) \in g$. Thus $h \subseteq g$.

Since $g \subseteq h$ and $h \subseteq g$, it follows that $g = f$.

(b)

I was not able to do it. Using the solution directly from the book.

Suppose $c_1, c_2 \in C$ such that $c_1 \ne c_2$. Suppose $b ∈ B$. Suppose $g$ and $h$ are functions from $B \to C$ such that $\forall x \in B(g(x) = c_1)$,
$\forall x \in B \setminus \{b\}(h(x) = c_1)$, and $h(b) = c_2$ . Then $g \ne h$, so by assumption(by contrapositive) $g \circ f \ne h \circ f$, and therefore we can choose some $a \in A$ such that $g(f(a)) \ne h(f(a))$. But by the way $g$ and $h$ were defined, the only $x \in B$ for which $g(x) \ne h(x)$ is $x = b$, so it follows that $f(a) = b$. Since $b$ was arbitrary, it follows that $f$ is onto.

Soln18

(a) Suppose $a \in A$ and $b \in B$ such that $(a,b) \in g$. Since $f$ is a function frm $B$ to $C$ and $b \in B$, there exist an element say $c \in C$ such that $(b,c) \in f$. Since $(a,b) \in g$ and $(b,c) \in f$, it follows that $(a,c) \in f \circ g$. Since $f \circ g = f \circ h$, it follows $(a,c) \in f \circ h$. Thus there exist element $b' \in B$ such that $(a,b') \in h$ and $(b',c) \in f$. Since $(b',c) \in f$ and $(b,c) \in f$ and $f$ is one-to-one, it follows that $b' = b$. Sicne $b = b'$ and $(a,b') \in h$, it follows $(a,b) \in h$. Since $(a,b)$ is arbitrary, it follows that $g \subseteq f$.

Similarly it can be seen that $f \subseteq g$.

Thus we have $f \subseteq g$ and $g \subseteq f$, it follows that $f = g$.

(b)

Suppose $b_1, b_2 \in B$ such that $f(b_1) = f(b_2)$. Suppose $g$ and $h$ are functions from $A \to B$ such that $\forall x \in A(g(x) = b_1)$,
$\forall x \in A(h(x) = b_2)$. Thus $f \circ g (x) = f(g(x)) = f(b_1) = f(b_2) = f(h(x)) = f \circ h(x)$. Since it is given that if $f \circ g = g \circ f$, then $g = h$, it follows that $g(x) = h(x)$. Thus $b_1 = b_2$. Thus $f$ is one-to-one.

Soln19

(a)

Proof for $hRf$:

Suppose $t(x) = x^2 - 2x + 2$ is a function on $\mathbb R \to \mathbb R$. Thus $t \circ f(x) = t(f(x)) = (x^2 + 1)^2 - 2(x^2 + 1) + 2$. Thus we have $t \circ f(x) = x^4 + 1 + 2x^2 - 2x^2 - 2 + 2 = x^4 + 1 = h(x)$. Thus there exist a function $t(x) = x^2 - 2x + 2$ such that $h = t \circ f$. Thus $hRf$.

Proof for $\lnot gRf$:

We can prove this by contradiction. Suppose that $t(x): \mathbb R \to \mathbb R$ such that $t \circ f = g$. Thus $t(f(x)) = g(x)$. Thus for $x = x_0 = -1$, $g(x_0) = 0$. Since $g(x) = t(f(x))$, it follows that $f(x) = x_0 = -1$. Since $f(x) = x^2 + 1$, it follows that $\forall x \in \mathbb R(f(x) \ge 1)$. Thus there is no value of $x \in \mathbb R$ such that $f(x) = -1$. Thus $t(f(x)) \ne g(x)$ at $x = x_0 = -1$. This contradicts that $t \circ f$ is a function on $\mathbb R \to \mathbb R$. Thus $(g,f) \notin R$.

(b)

A relation is preorder if it is reflexive and transitive.

Proof of $R$ is reflexive:

Suppose $f \in \mathcal F$. Consider $i_{\mathbb R} \circ f(x) = i_{\mathbb R}(f(x)) = f(x)$. Thus there exist a function $i_{\mathbb R}$ such that $i_{\mathbb R} \circ f = f$. Thus $(f,f) \in R$. Since $f$ is arbitrary, it follows that $R$ is reflexive.

Proof of $R$ is transitive:

Suppose $f,g,h \in \mathcal F$ such that $fRg$ and $gRh$. Since $fRg$, there exist a function $s$ such that that $f = s \circ g$. Similarly since $gRh$, it follows that for there exist a function $t$ such that $t \circ h = g$. Thus $f(x) = s(g(x)) = s(t \circ h(x)) = s(t(h(x)))$. Thus $f(x) = s(t(h(x))) = s \circ t(h(x)) = k(h(x))$, where $k = s \circ t$. Thus there exist a function $k$ such that $k \circ h = f$. Thus $(f,h) \in R$. Since $f,g,h$ are arbitrary, it follows that $R$ is transitive.

Since $R$ is reflexive and transitive, it follows that $R$ is pre-order.

(c)

Suppose $f \in \mathcal F$. Consider $f \circ i_{\mathbb R}(x) = f (i_{\mathbb R}(x)) = f(x)$. Thus there exist a function $f = f$ such that $f \circ i_{\mathbb R} = f$. Thus $(f,i_{\mathbb R}) \in R$.

(d)

($\to$) Suppose $i_{\mathbb R}Rf$. Suppose $x_1, x_2 \in \mathbb R$ such that $f(x_1) = f(x_2)$. Since $i_{\mathbb R}Rf$, there exist a function $t : \mathbb R \to \mathbb R$ such that $t \circ f = i_{\mathbb R}$. Thus $t \circ f(x_1) = t(f(x_1)) = t(f(x_2)) = t \circ f(x_2)$. Since $t \circ f = i_{\mathbb R}$, it follows that $t \circ f(x_1) = x_1$ and $t \circ f(x_2) = x_2$. Since $t \circ f(x_1) = t \circ f(x_2)$, it follows that $x_1 = x_2$. Since $x_1, x_2$ are arbitrary, it follows that $f$ is one-to-one.

($\leftarrow$) Suppose $f$ is one-to-one. Suppose $h = f^{-1} \cup \{ R \setminus A \times \{0\} \}$ where $A = Ran(f)$. Now we will first prove that $h$ is a function.

To prove $h$ is a function, we need to prove existence and uniqueness. Suppose $x \in R$. Thus we have two possible cases:

• Case 1: $x \in A$. Thus $x \in Ran(f)$. It follows there exist an element $y \in \mathbb R$ such that $(y,x) \in f$. Thus $(x,y) \in f^{-1}$. Also since $f$ is one-to-one, thus $x$ is an image of only one element $y$ in $f$. Thus for $x$ there is a unique element $y$ in $f^{-1}$. Thus $h(x)$ exists as well as if $x \in A$ then there is only one element(unique) $y$ such that $h(x) = y$.

• Case 2: $x \notin A$. Thus $x \in \mathbb R \setminus A$. Thus $h(x) = 0$. Thus there is a unique value $0$ for every $x \in \mathbb R \setminus A$. Thus for $x \notin A$, $h(x)$ exists and there is only one value(unique) $0$ such that $h(x) = 0$.

Thus $h$ is a function on $\mathbb R \to \mathbb R$.

Now suppose $x \in \mathbb R$ and $h \circ f(x) = h(f(x))$. Since $f(x) \in Ran(R)$, then by definition of $h$, $h(f(x)) = x$. Thus $h \circ f = i_{\mathbb R}$.

Thus there exist a function $h$ such that $h \circ f = i_{\mathbb R}$. Thus $i_{\mathbb R}Rf$.

(e)

Suppose $f \in \mathcal F$. We have $g \circ f(x) = g(f(x))$. Since $f$ is a function from $\mathbb R$ to $\mathbb R$, it follows that $f(x) \in \mathbb R$. Since $\forall x \in \mathbb R(g(x) = c)$ and $f(x) \in \mathbb R$, it follows that $g(f(x)) = c$. Since $g(x) = c$, it follows $g \circ f = g$. Thus $(g,f) \in R$.

(f)

($\to$) Suppose $fRg$. Thus there exist a function $h$ such that $h \circ g = f$. Thus $h(g(x)) = f(x)$. Since $g(x) = c$, it follows that $f(x) = h(c)$. Since $h(c)$ is a constant, thus $f(x) = h(c)$ is also a constant. Thus $f$ is a contant function.

($\leftarrow$) Suppose $f$ is a constant function such that $\forall x \in \mathbb R(f(x) = d)$. Consider $f \circ g = f(g(x)) = f(c) = d = f(x)$. Thus $f \circ g = f$. Thus $(f,g) \in R$, or $fRg$.

(g)

Proof for largest element:

Suppose $[l]_S \in \mathcal F / S$ is set of all one-to-one functions. Thus $l \in [l]_S$ and $l$ is one-to-one. Now to prove $[l]_S$ is the largest element, if we prove $\forall [f]_S \in \mathcal F / S([f]_S T [l]_S)$. Since it is given that $[f]_S T [g]_S$ iff $f R g$, it follows that we need to prove $f R l$.
Now from part(c) of this solution, we have $(f,i_{\mathbb R}) \in R$, or there exist a function $h$ such that $f = h \circ i_{\mathbb R}$. Also since $l$ is one-to-one, then form part(e) of the solution, there exist a function $k$ such that $i_{\mathbb R} = k \circ l$. Thus we have $f = h \circ i_{\mathbb R} = h \circ k \circ l = m \circ l$, where $m = h \circ k$. Thus $f R l$. It follows that $[f]_S T [l]_S$. Since $[f]_S$ is arbitrary, it follows that $[l]_S$ is the largest element of $\mathcal F / S$ in the partial order $T$.

Proof for smallest element:

Suppose $[s]_S \in \mathcal F / S$ is set of all constant functions. Thus $s \in [s]_S$ and $s$ is a contant function. Now to prove $[s]_S$ is the smallest element, if we prove $\forall [f]_S \in \mathcal F / S([s]_S T [f]_S)$. Since it is given that $[f]_S T [g]_S$ iff $f R g$, it follows that we need to prove $s R f$. Since $s$ is contant function, thus using part(e) of this solution, it follows that $s R f$. Thus $[f]_S T [s]_S$. Since $[f]_S$ is arbitrary, it follows that $[s]_S$ is the smallest element of $\mathcal F / S$ in the partial order $T$.